Pemberdayaan Pondok Pesantren Nurul Islam Sebagai Ikon Perubahan Masyarakat Di Kelurahan Antirogo Dalam Mewujudkan Program Desa Peduli Iklim - Afifudin Muhajir; Yeny Dhokhikah; Achmad Fauqi Aksan; Alisiyah Nurud Dhuha; Novita Febianti; Farhan Baehaqi Sholeh; Rahmat Taruna; Isna Ayu Nur Febriana; Hasyim Ashari Abdul M; Niar Pramiswari L.H; Anjana Supriyatna (Al-Ijtimā': Jurnal Pengabdian Kepada Masyarakat, 2024)
Nurul Islam Islamic Boarding School is an Islamic education institution in Antirogo Village, Sumbersari District, Jember Regency, East Java. Apart from being a means of education for the community, this Islamic boarding school can also create the potential for waste generation. The generation of waste in Islamic boarding school areas, especially from kitchens, can cause the earth's surface temperature to rise, resulting in climate change. Based on these problems, the service aimed to reduce the impact of waste generation by managing organic kitchen waste in urban farming products in the form of eco-enzyme and maggot cultivation. This service will occur from May 1, 2024, to November 1, 2024. This activity aims to empower Islamic boarding school residents, especially administrators and students. The method used in this service is designing Eco Enzyme fermentation tanks and maggot cultivation cages, creating a monitoring system, socializing and demonstrating tools, practising Eco Enzyme production and maggot cultivation, and program understanding tests. The results of this service activity are Urban Farming products in the form of Eco Enzyme and maggot solutions, which have been equipped with Eco Enzyme fermentation tanks and maggot cultivation cages. Another result is increasing knowledge among Islamic boarding school residents about managing organic waste in urban farming products to overcome climate change.